Study of Economic Viability of Floating Photovoltaic Electric Power in Indonesia. Issue 1 (March 2021) - Untoro, A A; Gunawan, T; Hidayanto, B D; Perkasa, F A; Wijaya, A A
Abstract: The government has already set target for utilisation of renewable energy to be achieved are at least 23% in 2025 and 31% in 2050. This study assesses the feasibility of the implementation utility scale Floating Solar PV in Indonesia based on technical and economic perspective. The analysis focused on the assessment of solar irradiation data, module efficiency to project electric production, followed by economic analysis on the parameter of the interest rate, debt to equity ratio, electric production, EPC Cost. In Indonesia, there is also incentives which are regulated to promote the infrastructure investment including renewable energy which are tax holiday, import tax exemption which can reduce the tariff. The investigation show that the effect the interest rate, debt to equity ratio, EPC Cost to the tariff and effect the incentive which are the tax holiday, import tax exemption to the tariff. which are evaluated for each area based on on assessment energy yield projection and dam identification to be compared to electrical generation cost (BPP Local and BPP National) where based on the simulation the electricity tariff of Floating Solar PV (4.9 – 5.8 cUSD/kWh) in each province is below the BPP